A Social Ecological Model of Syndemic Risk affecting Women with and At‐Risk for HIV in Impoverished Urban Communities. Issue 3 (14th September 2015) - Batchelder, A. W.; Gonzalez, J. S.; Palma, A.; Schoenbaum, E.; Lounsbury, D. W.
Abstract: Syndemic risk is an ecological construct, defined by co‐occurring interdependent socio‐environmental, interpersonal and intrapersonal determinants. We posited syndemic risk to be a function of violence, substance use, perceived financial hardship, emotional distress and self‐worth among women with and at‐risk for HIV in an impoverished urban community. In order to better understand these interrelationships, we developed and validated a system dynamics (SD) model based upon peer‐reviewed literature; secondary data analyses of a cohort dataset including women living with and at‐risk of HIV in Bronx, NY (N = 620); and input from a Bronx‐based community advisory board. Simulated model output revealed divergent levels and patterns of syndemic risk over time across different sample profiles. Outputs generated new insights about how to effectively explore multicomponent multi‐level programs in order to strategically develop more effective services for this population. Specifically, the model indicated that effective multi‐level interventions might bolster women's resilience by increasing self‐worth, which may result in decreased perceived financial hardship and risk of violence. Overall, our stakeholder‐informed model depicts how self‐worth may be a major driver of vulnerability and a meaningful addition to syndemic theory affecting this population.